Post-translational Modifications in Oral Bacteria and Their Functional Impact - Ma, Qizhao; Zhang, Qiong; Chen, Yang; Yu, Shuxing; Huang, Jun; Liu, Yaqi; Gong, Tao; Li, Yuqing; Zou, Jing (Frontiers in Microbiology, 2021)
Oral bacteria colonize the oral cavity, surrounding complex and variable environments. Post-translational modifications (PTMs) are an efficient biochemical mechanism across all domains of life. Oral bacteria could depend on PTMs to quickly regulate their metabolic processes in the face of external stimuli. In recent years, thanks to advances in enrichment strategies, the number and variety of PTMs that have been identified and characterized in oral bacteria have increased. PTMs, covalently modified by diverse enzymes, occur in amino acid residues of the target substrate, altering the functions of proteins involved in different biological processes. For example, Ptk1 reciprocally phosphorylates Php1 on tyrosine residues 159 and 161, required for Porphyromona gingivalis EPS production and community development with the antecedent oral biofilm constituent Streptococcus gordonii, and in turn Php1 dephosphorylates Ptk1 and rapidly causes the conversion of Ptk1 to a state of low tyrosine phosphorylation. Protein acetylation is also widespread in oral bacteria. In the acetylome of Streptococcus mutans, 973 acetylation sites were identified in 445 proteins, accounting for 22.7% of overall proteins involving virulence factors and pathogenic processes. Other PTMs in oral bacteria include serine or threonine glycosylation in Cnm involving intracerebral hemorrhage, arginine citrullination in peptidylarginine deiminases (PADs), leading to inflammation, lysine succinylation in P. gingivalis virulence factors (gingipains, fimbriae, RagB, and PorR), and cysteine glutathionylation in thioredoxin-like protein (Tlp) in response to oxidative stress in S. mutans. Here we review oral bacterial PTMs, focusing on acetylation, phosphorylation, glycosylation, citrullination, succinylation and glutathionylation, and corresponding modifying enzymes. We describe different PTMs in association with some examples, discussing their potential role and function in oral bacteria physiological processes and regulatory networks. Identification and characterization of PTMs not only contribute to understanding their role in oral bacterial virulence, adaption, and resistance but will open new avenues to treat oral infectious diseases.